RETROSPECTIVE STUDY OF 22 TPLO PROCEDURES IN DOGS WITH CRUCIATE LIGAMENT RUPTURE PERFORMED AT THE VETERINARY HOSPITAL OF THE FEDERAL UNIVERSITY OF PARANÁ - CURITIBA - Thyara Wwizenmann; Danilo Marques; Fernando Ibanez; Paula Fratini; Ana Hespanha (Revista de Ciência Veterinária e Saúde Pública, 2022)
Cranial cruciate ligament rupture is a closely studied disease currently being the leading cause of limb claudication in the dog. The diagnosis is clinical through the tibial compression test and drawer test. Cranial cruciate ligament rupture (CCrLR) is a common disease in dogs, being the most common cause of degenerative joint disease in the stifle. Surgical treatment allows stabilization of the joint, ensuring return of limb function, and reducing the progression of osteoarthritis. Several surgical techniques are described for the treatment of CCrLR, including osteotomy and leveling of the tibial plateau (TPLO). Although there are numerous references to the procedure, few studies have evaluated the results of TPLO.This study evaluated clinical and radiographic changes in the stifles of dogs following TPLO for CCrLR. The medical records of 22 dogs treated at the Veterinary Hospital of the Federal University of Paraná, which had undergone TPLO between June 2016 and March 2018, were retrospectively screened. The patients were evaluated preoperatively, and at 7, 14, 30 and 60 days after surgery to monitor clinical and radiographic progress. The pre and postoperative tibial plateau angle was evaluated, and the D1, D2 and D3 measurements in the immediate postoperative period. TPLO was shown to be effective for the treatment of cranial cruciate ligament rupture in this study.